Self studies the psychology of self and identity - Scheibe, Karl E. 1937- (Praeger Publishers, an imprint of Greenwood Publishing Group, Inc., 1995)
In this far-ranging study, Scheibe seeks an understanding of the self and personal identity. In doing so, he focuses on the various relationships of the self in social environments. He examines the major historical perspectives on the self, the process or processes of socialization, memory, and identity, and the psychology of national identity. A well-written look at the essential considerations affecting the self in its development, ongoing and changing identity, and its relationships to others and to institutions, this study will be of interest to scholars and researchers in psychology and sociology as well as the general reader.